Future-proofing the news : preserving the first draft of history - Hansen, Kathleen A., 1954-; Paul, Nora, 1953- (Lanham : Rowman & Littlefield, 2017)
News coverage is often described as the first draft of history. From the publication in 1690 of the first American newspaper, Publick Occurrences, to the latest tweet, news has been disseminated to inform its audience about what is going on in the world. But the preservation of news content has had it technological, legal, and organizational challenges. Over the centuries, as new means of finding, producing, and distributing news were developed, the methods used to ensure future generations' access changed, and new challenges for news content preservation arose. This book covers the history of news preservation (or lack thereof), the decisions that helped ensure (or doom) its preservation, and the unique preservation issues created by each new form of media. All but one copy of Publick Occurrences were destroyed by decree. The wood pulp-based newsprint used for later newspapers crumbles to dust. Early microfilm disintegrates to acid, and decades of microfilmed newspapers have already dissolved in their storage drawers. Early radio and television newscasts were rarely captured, and when they were, the technological formats for accessing the tapes have lone been superseded. Sounds and images stored on audio- and videotapes fade and become unreadable. The early years of web publication by news organizations were lost by changes in publishing platforms and a false security that everything on the Internet lives forever. In fifty or a hundred years, what will we be able to retrieve from today's news output? How will we tell the story of this time and place? Will we have better access to news produced in 1816 than news produced in 2016? These are some of the questions Future-Proofing the News aims to answer. -- Back cover.
Includes bibliographical references and index.
Keywords: Journalism -- United States -- History; Journalism -- Technological innovations -- United States; American newspapers -- History; Newspapers -- Conservation and restoration -- United States; Newspaper publishing -- United States -- History; Press law -- United States